Taxonomic review of the Dichotomius (Luederwaldtinia) agenor species group (Coleoptera: Scarabaeidae: Scarabaeinae) - Montoya-Molina, Santiago; Vaz-de-Mello, Fernando Z. (European Journal of Taxonomy, 2021)
The Neotropical D. agenor species group of the subgenus Luederwaldtinia Martínez, 1951 is taxonomically reviewed. After examination of specimens in collections, the D. agenor species group will consist of seventeen species, a leap from the former nine species: D. agenor (Harold, 1869), D. amplicollis (Harold, 1869), D. belus (Harold, 1880), D. centralis (Harold, 1869), D. deyrollei (Harold, 1869), D. sagittarius (Harold, 1869) stat. rev., D. tristis (Luederwaldt, 1923), D. triquetrus (Luederwaldt, 1923), D. validipilosus (Luederwaldt, 1931), D. fornicatus (Luederwaldt, 1931) [transferred to D. lucasi species group and to which D. bosqi (Pereira, 1941) is considered to be a new synonym], D. inachoides (Felsche, 1901) [transferred from the group fisus (Selenocopris)], D. simplicicornis (Luederwaldt, 1935) [transferred from the group fisus (Selenocopris)], D. subaeneus (Castelnau, 1840) [transferred from the D. carbonarius species group], D. rafanunezi sp. nov. from Mato Grosso, D. henripittieri sp. nov. from Venezuela and D. enioi sp. nov. from Guatemala and Costa Rica. This review was based on external morphology and characters of the male genitalia (aedeagus and internal sac). Descriptions of new species and redescriptions were made after examining the type-specimens of the already described species. Lectotype designations, species revalidations, redescriptions and new species descriptions are provided.